Impact of dietary deviation on disease progression and gut microbiome composition in lupus‐prone SNF1 mice. (August 2015) - Johnson, B. M.; Gaudreau, M.‐C.; Al‐Gadban, M. M.; Gudi, R.; Vasu, C.
Summary Environmental factors, including microbes and diet, play a key role in initiating autoimmunity in genetically predisposed individuals. However, the influence of gut microflora in the initiation and progression of systemic lupus erythematosus (SLE) is not well understood. In this study, we have examined the impact of drinking water pH on immune response, disease incidence and gut microbiome in a spontaneous mouse model of SLE. Our results show that (SWR × NZB) F1 (SNF1) mice that were given acidic pH water (AW) developed nephritis at a slower pace compared to those on neutral pH water (NW). Immunological analyses revealed that the NW‐recipient mice carry relatively higher levels of circulating autoantibodies against nuclear antigen (nAg) as well as plasma cells. Importantly, 16S rRNA gene‐targeted sequencing revealed that the composition of gut microbiome is significantly different between NW and AW groups of mice. In addition, analysis of cytokine and transcription factor expression revealed that immune response in the gut mucosa of NW recipient mice is dominated by T helper type 17 (Th17) and Th9‐associated factors. Segmented filamentous bacteria (SFB) promote a Th17 response and autoimmunity in mouse models of arthritis and multiple sclerosis. Interestingly, however, not only was SFB colonization unaffected by the pH of drinking water, but also SFB failed to cause a profound increase in Th17 response and had no significant effect on lupus incidence. Overall, these observations show that simple dietary deviations such as the pH of drinking water can influence lupus incidence and affect the composition of gut microbiome.